Clinical relevance of SARS-CoV-2 infection in late pregnancy - Marta Ruggiero; Edgardo Somigliana; Beatrice Tassis; Letizia Li Piani; Sara Uceda Renteria; Giussy Barbara; Giovanna Lunghi; Carlo Pietrasanta; Enrico Ferrazzi (BMC, 2021)
Abstract Background Evidence on the outcome of SARS-CoV-2 infection in pregnancy is generally reassuring but yet not definitive. Methods To specifically assess the impact of SARS-CoV-2 infection in late pregnancy, we prospectively recruited 315 consecutive women delivering in a referral hospital located in Lombardy, Italy in the early phase of the epidemic. Restriction of the recruitment to this peculiar historical time period allowed to exclude infections occurring early in pregnancy and to limit the recall bias. All recruited subjects underwent a nasopharyngeal swab to assess the presence of Sars-Cov-2 using Real-time PCR. In addition, two different types of antibodies for the virus were evaluated in peripheral blood, those against the spike proteins S1 and S2 of the envelope and those against the nucleoprotein of the nucleocapsid. Women were considered to have had SARS-CoV-2 infection in pregnancy if at least one of the three assessments was positive. Results Overall, 28 women had a diagnosis of SARS-CoV-2 infection in pregnancy (8.9%). Women diagnosed with the infection were more likely to report one or more episodes of symptoms suggestive for Covid-19 (n = 11, 39.3%) compared to unaffected women (n = 39, 13.6%). The corresponding OR was 4.11 (95%CI: 1.79-9.44). Symptoms significantly associated with Covid-19 in pregnancy included fever, cough, dyspnea and anosmia. Only one woman necessitated intensive care. Pregnancy outcome in women with and without SARS-CoV-2 infection did not also differ. Conclusions SARS-CoV-2 infection is asymptomatic in three out of five women in late pregnancy and is rarely severe. In addition, pregnancy outcome may not be markedly affected.